Association between demographic and radiographic characteristics of the schneiderian membrane and periapical and periodontal diseases using cone-beam computed tomography scanning: A retrospective study - Azin Khorramdel; Adileh Shirmohammadi; Alireza Sadighi; Masoumeh Faramarzi; Amir Reza Babaloo; Mehrnoosh Sadighi Shamami; Amin Mousavi; Zia Ebrahim Adhami (Tabriz University of Medical Sciences, 2017)
Background. This study was undertaken to assess the pathological and spatial associations between periapical and periodontal diseases of the maxillary first molars and thickening of maxillary sinus mucosa with cone-beam computed tomography. Methods. A total of 132 CBCT images of subjects 20‒60 years of age were evaluated retrospectively. The patients' sex and age and demographic and pathologic findings of the maxillary sinus in the first molar area were recorded, graded and analyzed. Results. Approximately 59% of patients were male and 41% were female, with no significant difference in the thickness of schneiderian membrane between males and females. Based on the periapical index scoring, the highest frequency was detected in group 1. Based on the results of ANOVA, there were no significant differences in the frequencies of endodontic‒periodontal lesions and an increase in schneiderian membrane thickness. There were significant relationships between periapical and periodontal infections (P<0.001) and schneiderian membrane thickness. Furthermore, a significant relationship was detected between the thickness of the schneiderian membrane and the distance between the sinus floor and the root apices (P=0.38). Conclusion. A retrospective inspection of CBCT imaging revealed that periapical lesions and periodontal infections in the posterior area of the maxilla were associated with thickening of the schneiderian membrane. In addition, there was a significant relationship between the location of maxillary posterior teeth, i.e. the thickness of bone from the root apex to the maxillary sinus floor, and schneiderian membrane thickness.